2021
DOI: 10.1109/jsen.2021.3068922
|View full text |Cite
|
Sign up to set email alerts
|

Flex Printed Circuit Board Implemented Graphene-Based DNA Sensor for Detection of SARS-CoV-2

Abstract: Since the COVID-19 outbreak was declared a pandemic by the World Health Organization (WHO) inMarch 2020, ongoing efforts have been made to develop sensitive diagnostic platforms. Detection of viral RNA provides the highest sensitivity and specificity for detection of early and asymptomatic infections. Thus, this work aimed at developing a label-free genosensor composed of graphene as a working electrode that could be embedded into a flex printed circuit board (FPCB) for the rapid, sensitive, amplificationfree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…Similar to the previous approach, another case of a flex printed circuit board (FPCB) DNA sensor for the detection of SARS-CoV-2 was reported (Damiati et al, 2021) using graphene as a working electrode, based on the hybridization of the captured DNA molecule using a simple streptavidinbiotin interaction platform. The functionalized electrode was then used to test the detection capability against a synthetic strand of ssDNA, which is similar to the ORF1ab sequence of the SARS-CoV-2 virus.…”
Section: Electrochemical Sensing Of Covid-19mentioning
confidence: 96%
“…Similar to the previous approach, another case of a flex printed circuit board (FPCB) DNA sensor for the detection of SARS-CoV-2 was reported (Damiati et al, 2021) using graphene as a working electrode, based on the hybridization of the captured DNA molecule using a simple streptavidinbiotin interaction platform. The functionalized electrode was then used to test the detection capability against a synthetic strand of ssDNA, which is similar to the ORF1ab sequence of the SARS-CoV-2 virus.…”
Section: Electrochemical Sensing Of Covid-19mentioning
confidence: 96%
“…In a similar approach, Damiati et al reported a flex printed circuit board (FPCB)-based genosensor for the quick, sensitive, amplification-free, and label-free detection of SARS-CoV-2 with a predicted LOD of ∼33 fg/mL (equal to around 5 × 0 5 copies/µL or 0.17 fM) in 30 min [87]. The sensor comprises a graphene working electrode and small easy-to-use reservoir chamber embedded into FPCB.…”
Section: Isothermal Nucleic Acid Amplification Tests (Inaats)mentioning
confidence: 99%
“…They were able to get a LOD of roughly 100 fg mL À1 . 139 Another label-free impedance biosensor utilizing the screen-printing method was reported by Ehsan et al to detect SARS-CoV-2. They demonstrated a low-cost batch production process for a cellulose paper substrate.…”
Section: God(fad) + Glucose God (Fadhmentioning
confidence: 99%